Boganmeldelser - Peter Kramp; Dorte Sestoft; Joi Bay; Karsten Ingvaldsen; Britta Kyvsgaard; Beth Grothe Nielsen; Thomas Hammerbrink; Ragnheiður Bragadóttir (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews